Streamlined best estimate plus uncertainty analysis of a GEN III + BWR for a bottom drain line small break LOCA. (April 2023) - Zhang, Xueyan; Deng, Chengcheng; Hu, Mengyan; Zhang, Yixuan; Peng, Cuiting; Yang, Jun
Highlights: A Streamlined BEPU method was proposed to summarize some efficient elements of previous BEPU methods, and is a flexible approach that could still be a valuable analysis process when only part of it was conducted. The active flowchart of Streamlined BEPU was established in a Model-Based Systems Engineering form with active button to generate PIRT. This method was demonstrated on the Bottom Drain Line Break accident in a GEN III + BWR with sensitivity analysis. Abstract: Best Estimate Plus Uncertainty analysis has been used in the design, certification, and safety review of Nuclear Power Plants. To analyze the small break loss of coolant accident of a Generation III + Boiling Water Reactor, a streamlined BEPU method has been established and partially demonstrated to a Bottom Drain Line small break Loss Of Coolant Accident post-test analysis in this investigation. A RELAP5 input model was built for an integral test facility simulating a Generation III + Reactor with passive safety features. The Fast Fourier Transform Based Method was utilized to preliminarily evaluate the accuracy of the code simulation results. The DAKOTA toolkit was utilized to drive uncertainty quantification and sensitivity analysis. The simulation results generally reproduce the experimental phenomenon observed during experiments. The uncertainty bands of output parameters were established to demonstrate the enclosing of experimental data and the safety margin according to the design limits.